Draft Genome Sequence of an Escherichia coli Strain Harboring blaCTX-M-115, blaCMY-2, Aminoglycoside, Tetracycline, and Sulfonamide Resistance Genes, Isolated from a Costa Rican Wastewater Treatment Plant - Barrantes Jiménez, Kenia (2020)
We report the draft genome sequence of the multidrug-resistant Escherichia coli strain PTA A1517-5, isolated from a wastewater treatment plant in Costa Rica. The genome consists of 4,927,375 bp with a GC content of 50.57% and a total of 4,853 genes. This strain harbors blaCTX-M-115, blaCMY-2, aminoglycoside, tetracycline, and sulfonamide resistance genes.